Purification of axonin-1, a protein that is secreted from axons during neurogenesis. - Ruegg, M A (1989)
Using selective metabolic labelling in a compartmental cell culture system two proteins, denoted axonin-1 and axonin-2, were found to be secreted by axons of dorsal root ganglia neurons from chicken embryos. Based on its characteristic coordinates and spot morphology in two-dimensional gel electrophoresis, axonin-1 was detected in the cerebrospinal fluid and the vitreous fluid, axonin-1 was purified 476-fold to homogeneity by a four-step chromatographic procedure. The identity of the purified protein as axonin-1 was confirmed by immunological methods. Axonin-1 is a glycoprotein that subdivides into at least 16 immunologically similar isoelectric variants; their molecular weight range extends from 132 to 140 kd and their pI range from 5.3 to 6.2. In the vitreous fluid of the embryo, axonin-1 could first be detected on the embryonic day 5 and highest concentrations were measured during the second half of embryonic life; in the vitreous fluid of the adult chicken, concentrations were approximately 20 times lower. The early onset of secretion and the time course of expression suggest a role for axonin-1 in the development of the nervous system.